(untitled) (Research, Society and Development, 2020)
The aim of the study was to characterize the clinical injuries attended by a Mobile Emergency Care Service and the factors associated with the destinations of the consultations performed. Retrospective documentary survey was carried out in service bulletins of the Mobile Emergency Care Service of a municipality in the south of Brazil, from November 2015 to May 2016. For the data collection a structured script was used, which included the information from service bulletins. The Poisson regression analysis was used to evaluate the risk of clinical injuries in the destination of care. There were 1,748 consultations for clinical injuries. Neurological injuries were the most attended. Patients with clinical injuries have a 731% higher risk of remaining in the place after care. The greater risk of staying in the place after attending to medical conditions, indicates that although it is a service designed for the attention of emergencies, it is often triggered by the availability of doctors and medications, demonstrating that the population is unaware of the real function this service.